Pengaruh Model Pembelajaran E-Learning dan Bimbingan Orang Tua terhadap Hasil Belajar Bidang Studi Fiqih di Masa Covid-19 - Fithida Yati (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
Learning success is influenced by factors that exist outside the individual (students), such as the family, school, and community environment. An example of an external factor namely the application of e-learning in schools as a learning model solution during Covid-19. In addition, parental guidance is also important in growing their physical and mental strength. This study aims to determine the effect of e-learning outcomes in the field of jurisprudence during the covid-19 period MTsN 1 Pesisir Selatan. This type of research used is quantitative with associative method, namely to review the significance of the influence between variables and other variables that influence it. The results of the study revealed; 1) The application of the e-learning model to fiqh learning has a significant effect on learning outcomes in the field of fiqh (Y) during the covid-19 period at MTsN 1 Pesisir Selatan with a linear X1 and Y relationship; 2) Parental guidance has a significant effect on learning outcomes in the field of jurisprudence during the covid-19 period at MTsN 1 Pesisir Selatan, the relationship between X2 and Y is linear; and 3) The e-learning learning model and parental guidance in learning both have a significant effect on learning outcomes in the field of jurisprudence during the Covid-19 period at MTsN 1 Pesisir Selatan with a linear X1, X2 and Y relationship.